Triggering the internationalization of Malaysian quantity surveying firms - Wang, Chen; Wood, Lincoln C.; Abdul-Rahman, Hamzah; Ng, Han Biao (Springer Verlag, 2017)
Although there is an increasing trend of services being traded across borders, quantity surveying (QS) firms in the construction sector remain under-researched. The triggers for the increasing globalization of QS firms are not clear, nor how these triggers are perceived by managers at different levels. A questionnaire was administered in over 84 QS consultancy firms, and the results were analyzed using the repertory grid technique, allowing a comparison between the general respondents and a focus group of senior managers. The findings show that senior managers with significant experience realize the importance of a strong internal capability of the QS firm and the capability to develop innovative offerings, coupled with an awareness of the target market and the ability to secure revenue through key contracts. Firm- and location-specific factors were more important than other competitive advantages or foreign markets’ characteristics when deciding to globalize.